Accessibility, inclusion and assistive technology: a bibliometric study - Camila Dias de Oliveira; Daniel Mill (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
This paper aims to investigate how the issue accessibility, inclusion and assistive technology have been worked in scientific researches of the education area. With goal to answer the question: how representative is the scientific production carried out on this subject? We consider the bibliometric research an appropriate methodology for the study and we used a group of thesis based on the area of education, structured by Group of Studies and Research on Innovation in Education, Languages and Technologies (Grupo Horizonte). At the end it was concluded that, although the themes are essential to the educational field of knowledge, few researchers deal with the subject, especially regarding to the use of assistive technologies in schools or in the perspective of accessibility.